Role of the clinical pharmacist in detection of drug therapy problemas in critically impatients: experience report - Alves, Gabrielle Mari Rosetti [UNESP]; Varallo, Fabiana Rossi [UNESP]; Lucchetta, Rosa Camila; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2014)
This is an experience report on clinical pharmacy in New York, United States of America, in a teaching hospital, describing the results of drug therapy monitoring in critically ill patients, as well as interventions to solve or prevent identified drug therapy problems. The cross-sectional study was conducted by the clinical staff at the Surgical Intensive Care Unit during August 20th to 24th, 2012. Blood counts, serum levels of certain antibiotics, microbiological cultures and their antibiotic susceptibility, possible drug interactions, dosage of each drug prescribed and the compatibility between the route of administration and pharmaceutical form were assessed daily through review of electronic medical records. Twenty seven patients were followed up and 16 drug therapy problems were identified: Unnecessary drug therapy (seven), adverse drug reaction (four), needs additional drug therapy (two), noncompliance (two) and dosage too low (one). After evaluation, the drug therapy problems and their pharmaceutical interventions were reported to clinical pharmaceutical responsible for the Surgical ICU, as well as the multidisciplinary team. Further, the clinical outcomes were monitored and interventions were classified as to its acceptance. Data demonstrate that clinical pharmacists can contribute to the security and proper use of medications, as the trigger tools for intensive monitoring helps in early detection of drug therapy problems and patient safety.
Keywords: Patient safety; Pharmacovigilance; Drug-related side effects and adverse reactions; Intensive Care Units